Menarche dan Pengetahuan Menstruasi Santri: Studi Kasus Di Pondok Pesantren Mabda'ul Ma'arif dan As-Sunniyah Kencong Jember: Menarche and Menstrual Knowledge among Female Islamic Boarding School Students: A Case Study at Mabda'ul Ma'arif and As-Sunniyah Islamic Boarding Schools, Kencong, Jember - H. Sutrisno RS (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2004)
The onset of menarche and the variability in menstrual duration among adolescent girls remain underexplored in Islamic boarding school contexts, particularly when doctrinal fiqh teachings intersect with empirical biological realities. This study addresses the gap between classical Syafi’i texts, which specify a minimum menarcheal age of nine lunar years, and the actual menarcheal ages observed among female santri. The research aims to determine the age of menarche, the length of menstruation, and the sources of menstrual knowledge among santri. A descriptive qualitative case study was conducted at PP Mabda’ul Ma’arif and PP As-Sunniyah, involving 100 respondents selected through random sampling. Data were collected via closed-ended questionnaires, interviews with caregivers and teachers, and documentation. The findings reveal that menarche occurs between 11 and 15 solar years, with most santri menstruating for 6 to 7 days, though durations up to 15 days were recorded. While 98% of respondents knew about menstruation before menarche, 87% experienced anxiety at first menstruation. All santri understood religious prohibitions during menstruation, yet only 50% could distinguish between haid and istihadlah blood. Menstrual knowledge is acquired through formal schooling, sorogan, and wetonan. The study recommends using visual aids to teach about blood characteristics and deepening santri’s understanding of menstrual jurisprudence. Permulaan menarche dan variasi durasi menstruasi pada remaja putri masih kurang diteliti dalam konteks pesantren, khususnya ketika ajaran fikih klasik berhadapan dengan realitas biologis empiris. Penelitian ini mengatasi kesenjangan antara teks mazhab Syafi’i yang menetapkan batas minimal usia haid sembilan tahun qamariyah dengan usia menarche aktual yang diamati pada santri putri. Tujuan penelitian adalah mengetahui usia menarche, lama menstruasi, dan sumber pengetahuan menstruasi santri. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan jenis studi kasus di PP Mabda’ul Ma’arif dan PP As-Sunniyah. Sampel sebanyak 100 responden diambil secara random sampling. Data dikumpulkan melalui angket tertutup, wawancara dengan pengasuh dan ustadz, serta dokumentasi. Hasil penelitian menunjukkan menarche terjadi pada usia 11–15 tahun syamsiah, umumnya menstruasi berlangsung 6–7 hari, namun terdapat durasi hingga 15 hari. Sebanyak 98% santri mengetahui menstruasi sebelum menarche, tetapi 87% mengalami kecemasan saat menarche. Seluruh santri memahami larangan saat haid, namun hanya 50% mampu membedakan darah haid dan istihadlah. Pengetahuan menstruasi diperoleh dari sekolah, sorogan, dan wetonan. Penelitian merekomendasikan penggunaan alat peraga untuk mengajarkan karakteristik darah dan pendalaman fikih menstruasi bagi santri.